2019
DOI: 10.9755/ejfa.2018.v30.i12.1879
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cultivation methods on the chemical and nutritional characteristics of Lentinula edodes

Abstract: Lentinula edodes (Shiitake) is an edible mushroom with excellent nutritional potential, aroma and flavor. It’s traditionally produced on wood logs, but this practice has been replaced by cultivation on axenic substrates (AS) made from different materials that are stored in plastic bags. This papper aimed to evaluate the nutritional composition of L. edodes grown on Quercus acutíssima (QA) and AS by correlating their chemical composition with the media on which they were grown. Culture media were analyzed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our analysis revealed that the Ab contained trace amounts of toxic metals. The origin of the toxic metals may have been from the substrate where the mushroom was cultivated, (e.g., Bach et al, 2018). However, the levels detected were negligible and did not have any significant impact on our results, except for ALT enzyme; this biomarker isolated increased in the Ab group.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis revealed that the Ab contained trace amounts of toxic metals. The origin of the toxic metals may have been from the substrate where the mushroom was cultivated, (e.g., Bach et al, 2018). However, the levels detected were negligible and did not have any significant impact on our results, except for ALT enzyme; this biomarker isolated increased in the Ab group.…”
Section: Discussionmentioning
confidence: 99%
“…MAZ×AT Farklı ağaç türlerine ait kütüklerden elde edilen shiitake mantarlarının protein ve mineral madde içeriklerindeki farklılığın ağaç türlerine bağlı olarak kütüklerin besin içeriklerindeki değişimden kaynaklandığı düşünülmektedir. Farklı tarımsal atıkların kullanıldığı yetiştirme ortamlarından elde edilen shiitake mantarının protein ve mineral madde miktarlarının farklı olması da ortamların içeriklerinin etkisinden kaynaklanmaktadır [4,25,41,42]. Mantarlarda element bileşimini, substratın kimyasal bileşimi ve özellikleri yanında, ortamın eser elementlerle kirlenmesi de etkilemektedir [43].…”
Section: The Effects Of Different Mycelial Inoculation Times and Tree...unclassified
“…Therefore, it is necessary to discover more ways to get high‐quality, healthier protein. Edible mushrooms provide high‐quality proteins and present more productivity and biological efficiency than animals as a protein resource (Fabiane et al, 2018). These mushrooms are rich in dietary fiber, minerals, and vitamins and have a low lipid content, abundant amino acids, and a high proportion of polyunsaturated fatty acids (Jonathan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%